2001
DOI: 10.1007/bf02706714
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of indium antimonide and gallium antimonide crystals

Abstract: Indium antimonide and gallium antimonide were synthesized from the respective component elements using an indigenously fabricated synthesis unit. Bulk crystals of indium antimonide and gallium antimonide were grown using both the vertical and horizontal Bridgman techniques. Effect of ampoule shapes and diameters on the crystallinity and homogeneity was studied. The grown crystals were characterized using X-ray analysis, EDAX, chemical etching, Hall effect and conductivity measurements. In the case of gallium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…In the Bridgman technique, the conical shape of the ampoule is an important parameter, since conical tip in the ampoule is the point of initiation of the solidification and controls further growth. 15 Researchers reported that the ampoules with cone angles in the range [15][16][17][18][19][20][21][22][23][24] are found to be the most optimum to obtain inclusion-free good quality transparent crystals. [16][17][18] Here we selected the cone angle of [19][20][21][22][23] for the double wall ampoule for the growth of benzil single crystals.…”
Section: Methodsmentioning
confidence: 99%
“…In the Bridgman technique, the conical shape of the ampoule is an important parameter, since conical tip in the ampoule is the point of initiation of the solidification and controls further growth. 15 Researchers reported that the ampoules with cone angles in the range [15][16][17][18][19][20][21][22][23][24] are found to be the most optimum to obtain inclusion-free good quality transparent crystals. [16][17][18] Here we selected the cone angle of [19][20][21][22][23] for the double wall ampoule for the growth of benzil single crystals.…”
Section: Methodsmentioning
confidence: 99%
“…The bulk crystal growth of GaSb, GaSb:Se and GaSb:Zn was carried out using a Bridgman method [10]. The PA spectra were taken using FTIR spectrometer Nicolet NEXUS 670.…”
Section: Methodsmentioning
confidence: 99%
“…These have stimulated a lot of interest in GaSb for basic research as well as device fabrication. GaSb is the basic material for a variety of lattice parameter matched III-V compounds having band gaps ranging from 0.3 to 1.58 eV (corresponding to wavelengths of 0.8 to 4.3 µm) [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…GaSb based binary and ternary alloys have turned out to be important candidates for applications in long wavelength lasers and photodetectors for fiber optic communications [7]. InSb has been interested in high speed applications for transistors and other devices [8,9], which is associated directly with the very low electron effective mass and high mobility [10].…”
Section: Introductionmentioning
confidence: 99%